2011
DOI: 10.1038/emboj.2011.354
|View full text |Cite
|
Sign up to set email alerts
|

OCRL controls trafficking through early endosomes via PtdIns4,5P2-dependent regulation of endosomal actin

Abstract: Mutations in the phosphatidylinositol 4,5-bisphosphate (PtdIns4,5P(2)) 5-phosphatase OCRL cause Lowe syndrome, which is characterised by congenital cataracts, central hypotonia, and renal proximal tubular dysfunction. Previous studies have shown that OCRL interacts with components of the endosomal machinery; however, its role in endocytosis, and thus the pathogenic mechanisms of Lowe syndrome, have remained elusive. Here, we show that via its 5-phosphatase activity, OCRL controls early endosome (EE) function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
257
6
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(291 citation statements)
references
References 81 publications
27
257
6
1
Order By: Relevance
“…We examined the effects of CFTR depletion on the endocytic trafficking of two surface receptors: (i) the transferrin receptor (TfR), which recycles from the early/recycling endosomes to the PM 44 and (ii) the epidermal growth factor receptor (EGFR), which is sorted from the early endosomes towards degradative compartments (late endosomes (LEs)/lysosomes) following EGF-induced internalization. [45][46][47] As compared with scrambled siRNA-treated cells, CFTR-depleted 16HBE14o-cells exhibited reduced PM binding of Tf at 4 1C (Figure 3a), along with reduced cellular uptake of Tf (Figures 3b and c). This reduced uptake was due to impaired exposure of TfR to the cell surface rather than due to a defect in the internalization process per se (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the effects of CFTR depletion on the endocytic trafficking of two surface receptors: (i) the transferrin receptor (TfR), which recycles from the early/recycling endosomes to the PM 44 and (ii) the epidermal growth factor receptor (EGFR), which is sorted from the early endosomes towards degradative compartments (late endosomes (LEs)/lysosomes) following EGF-induced internalization. [45][46][47] As compared with scrambled siRNA-treated cells, CFTR-depleted 16HBE14o-cells exhibited reduced PM binding of Tf at 4 1C (Figure 3a), along with reduced cellular uptake of Tf (Figures 3b and c). This reduced uptake was due to impaired exposure of TfR to the cell surface rather than due to a defect in the internalization process per se (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding whether other diseaserelevant proteins might orchestrate proteostasis in their specific context could unveil new strategies for drug discovery in other conformational diseases. 16HBE14o-cells were transfected with GFP-tagged FYVE domain of SARA (PtdIns3P probe, GFP-FYVE) 46 and then with CFTR-specific or scrambled siRNAs or incubated with CFTR inh-172 for 24 h (20 mM, refreshed every 4 h, Calbiochem, Darmstadt, Germany) in the presence or absence of cystamine (250 mM, SigmaAldrich, St Louis, MO, USA) or EUK-134 (50mg/ml, Vinci-biochem, Florence, Italy) or HA-BECN1 overexpression 24 or scrambled or SQSTM1 siRNA. The cells were also treated with CFTR siRNA or CFTR inh172 and incubated with cystamine in presence of BECN1, hVps34, hVps15 or ATG14 siRNAs or with cystamine with/ without 3-MA (3 mM, Sigma-Aldrich).…”
Section: Discussionmentioning
confidence: 99%
“…53,56,57 Recycling defects in LS patient proximal tubule cells lead to low cell surface levels (and endosomal accumulation) of the multiligand receptor megalin and explains the low molecular weight (LMW) proteinuria characteristic of LS patients. 54 This phenotype in kidney cells was also confirmed by knockdown (KD) of Ocrl1 in the HK2 and MDCK cell lines. A recent study showed in vivo evidence in Ocrl1 -/-zebrafish of defective megalin recycling and hence reduced uptake of its ligand RAP.…”
Section: Vesicle Trafficking and Cilium Assemblymentioning
confidence: 72%
“…[52][53][54] In addition, mannose-6-phosphate receptor (M6PR) missorting to the plasma membrane was also observed upon Ocrl1 deficiency. 54,55 Although some authors found no major defects in uptake of transferrin, epidermal growth factor, and low-density lipoprotein upon Ocrl1 deficiency, other studies described aberrant endocytic vesicles and abnormal internalization.…”
Section: Vesicle Trafficking and Cilium Assemblymentioning
confidence: 99%
See 1 more Smart Citation